2018
DOI: 10.1002/cepa.855
|View full text |Cite
|
Sign up to set email alerts
|

Joints in masonry walls

Abstract: A correct design project should not only control the load-bearing capacity and stability of the individual elements but also ensure proper cooperation between these elements. Connection of masonry walls is crucial for durability of the building, safety of its users, and thermal insulation of external walls. The design and construction process is successful only if loads can be transferred properly between the particular structural elements. The issue of joints between the walls and consequent transferring of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The current research is a part of the ongoing research project on the connections of walls made of AAC connected using the most popular fittings available on the market, as well as various types of meshes, mats and other elements that would connect walls with each other in a simple and effective way. Results of the past studies can be found in [ 12 , 13 , 14 ]. So far, the obtained knowledge and results are promising and encourage further work in the field of describing the work of the joint and the use of new methods of constructing joints, using other connectors, using more steel elements in a given weld and optimising the shape of steel flat bars.…”
Section: Introductionmentioning
confidence: 99%
“…The current research is a part of the ongoing research project on the connections of walls made of AAC connected using the most popular fittings available on the market, as well as various types of meshes, mats and other elements that would connect walls with each other in a simple and effective way. Results of the past studies can be found in [ 12 , 13 , 14 ]. So far, the obtained knowledge and results are promising and encourage further work in the field of describing the work of the joint and the use of new methods of constructing joints, using other connectors, using more steel elements in a given weld and optimising the shape of steel flat bars.…”
Section: Introductionmentioning
confidence: 99%
“…The review of tests on joints described in [6] showed the lack of comprehensive studies on the behaviour of wall joints. That did not only refer to walls made of autoclaved aerated concrete (AAC) masonry units, but also made of other masonry units.…”
Section: Introductionmentioning
confidence: 99%
“…The review of tests on joints described in the paper [1] showed the lack of comprehensive papers on the behaviour of wall joints. That did not only refer to walls made of AAC masonry units, but also made of other masonry units.…”
Section: Introductionmentioning
confidence: 99%